Weak inflation and threat of deflation in the euro area: Limits of conventional monetary policy - Kerstin Bernoth; Marcel Fratzscher; Philipp König (DIW Economic Bulletin, 2014)
Inflation in the euro area has been below the European Central Bank's target for almost a year now and it is also expected to remain at a very low level in the near future. On the one hand, such a low level of inflation is not in line with the ECB's objective. On the other hand, there is the risk that this situation will lead to a slide into deflation. In view of the ECB's historically low policy rates, the question arises as to which monetary policy options are available. In order to counteract possible deflation, primarily unconventional measures remain open to the ECB, such as outright purchases of securities. But the onus is also on fiscal and economic policy to actively address low inflation and the risks of deflation.
Keywords: E00; E5; E6; 330; monetary policy; deflation; ECB; Euro Area